THE IMPLEMENTATION OF THE NUMBERED HEAD TOGETHER (NHT) COOPERATIVE LEARNING MODEL TO ENHANCE STUDENT LEARNING OUTCOMES IN THE TOPIC OF MECHANICAL MEASURING INSTRUMENTS AT SMKN 1 TUNJUNG TEJA - Triani, Nova; Iman, Atep; Ikhsanudin, Ikhsanudin (Universitas Negeri Surabaya, 2024)
In this study, the researchers want to find out how much better students learn mechanical measuring instruments when they use the NHT type of joint learning model compared to when they use the traditional model of learning at SMKN 1 Tunjung Teja. A non-equivalent control group approach is used in this kind of study, which is kind of like an experiment. The people who took part in this study were students in class X at TKRO SMKN 1 Tunjung Teja. A learning outcome test was used as a study tool, and the T-test and N-gain test were used to analyze the results. The results showed that the experimental class that used the NHT learning method learned a lot. They got an average score of 22.80 on the pretest and 90.80 on the posttest. The control class had an average score of 21.47 on the pre-test and 49.26 on the post-test for learning results. A significant value of 0.00 ? 0.05 was found when the independent sample t-test test was used to test the claim. The N-gain number for the experimental class was 88.10% with high criteria, while it was 35.71% for the control class with intermediate criteria. This shows that the students learned more. What this means is that using the NHT type group learning model makes learning about mechanical measuring tools much more effective.